Dampak Shock Nilai Tukar Riil terhadap Inflasi dan Current Account Indonesia - Darwanto, D (Jurnal Trikonomika, 2012)
Management change of currency exchange rate has implication in fluctuation conduct of exchange rate and domestic economy. This study aims to examine the impact of shock in exchange rate to macroeconomics variable such as, inflation, output, and current account in different exchange rate system in Indonesia. The method of this study is structural vector Autoregressive. The result of the study shows that management change of exchange rate system from managed floating exchange rate to free floating exchange rate does not change relationship path of exchange rate to inflation, output, and current account. The relationship path which is done shows that exchange rate depreciation to the variable above consistent with the theory. Depreciation of domestic exchange rate increases the inflation, output, and current account. However, a bit different result is seen from the influence of exchange rate depreciation to the output. In managed floating exchange rate period, the exchange rate depreciation will evoke the output contraction before finally increase in the output.